Engineering resilience with precast monolithic refractory articles. Issue 4 (23rd September 2019) - Goski, Dana; Lambert, Matthew
Abstract: Precast refractory ceramic shapes have had well‐known benefits over other refractory lining methods: consistent and controlled manufacturing processes with faster turnaround than traditional cast‐in‐place monolithic refractories, reduced labor cost over classic brick installations, and, if well designed, simple repair assemblies. By analyzing the common failure modes of precast monolithic shapes, a distinct method to enhance these advantages was theorized. Through modeling and in‐field testing, the use of multicomponent and heterogeneous composite refractory systems incorporating high‐temperature reinforcement structures increased reliability and provided more predictable modes of failure. Abstract : The benefits of precast refractory ceramic shapes are well known: consistent and controlled manufacturing processes with faster turnaround than traditional cast‐in‐place monolithic refractories, reduced labor over classic brick installations, and, if well designed, simple repair assemblies. The authors will present examples of multicomponent and heterogenous composite refractory systems incorporating high temperature reinforcement structures that can increase reliability and provide more predictable modes of failure.